Assessment of Quality of Multimodal Transportation for Containerized Exports. (January 2019) - Dua, Aman; Sinha, Deepankar
The twin paradigm of e-commerce and just-in-time has impelled the global markets for door-to-door service. Shippers do not particularly seek special modes of transport but rather demand performance of transport such as door-to-door service from the multimodal transport service (MTS) operators. Door-to-door service has also led to shift in common terms of trade such as free on board (FOB) and cost insurance freight (CIF) to delivery at place (DAP) or delivery duty paid (DDP) International Commercial Terms (incoterms). In such a case, the sellers are required to plan end-to-end rather than concentrate on port-to-port leg of the delivery process. Multimodal transportation (MMT) includes multiple modes of transport, multiple nodes (terminals) and numerous stakeholders. So far, researchers have focused on the attributes of MTS providers that affect expectations of customers. The present study looks into factors affecting performance of MTS. The approach cuts across the spectrum of qualitative to quantitative assessment. The authors, here, propose opinion mining to decipher the sentiments of clients of logistics service providers followed by open discussion (in a semi-structured format) to collate the soft and hard aspects of MMT chain. The findings of these exercises are used to frame a structured questionnaire for quantitative analysis. Four dimensions affecting quality of MMT have been identified, and one of them is found to be significant only under certain conditions. This article suggests implementation of an integrated digital ecosystem to enhance the quality of MMT in emerging markets like India.